2023
DOI: 10.1111/1467-8578.12453
|View full text |Cite
|
Sign up to set email alerts
|

Parental satisfaction with programmes provided for children with learning difficulties in Oman

Abstract: This study aimed to explore parental satisfaction with programmes provided for children with learning difficulties (LD) in Oman. A sample was collected from 299 parents who filled out an electronic self-reporting questionnaire during the second semester of 2021. The researchers designed a 19-item questionnaire that was distributed over two domains: 14 items on parent satisfaction and five items on parent co-operation. The results revealed that parents' overall satisfaction with the effectiveness of the LD prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The research community identified emerging disabled individuals from the S10-S9 category registered at the Baghdad Center for the Disabled for the year (2016), who numbered (20) male labs, according to the official records of the institute. As for the research sample, it was chosen intentionally from among them, as their number reached (6).…”
Section: Research Community and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The research community identified emerging disabled individuals from the S10-S9 category registered at the Baghdad Center for the Disabled for the year (2016), who numbered (20) male labs, according to the official records of the institute. As for the research sample, it was chosen intentionally from among them, as their number reached (6).…”
Section: Research Community and Samplementioning
confidence: 99%
“…foam boards(6), floats worn on the arms (for each laboratory (2)), Swedish chairs, rhythmic gymnastics hoops (6)).2.3.3 Means of collecting information1. Observation.…”
mentioning
confidence: 99%